A study on clinicopathological evaluation of rhinosporidiosis - Panda, Prangya; Sadangi, Bijaya Kumar; Jena, Dhaneswari; Panda, Sarita (International Journal of Research in Medical Sciences, 2017)
Background: Rhinosporidiosis is a chronic granulomatous disease. Aim of the study was to do a clinicopathological evaluation of the cases of rhinosporidiosis. Study design was longitudinal. Methods: The study was undertaken in MKCG medical college. 151 cases of rhinosporidiosis were taken. Pedunculated or sessile, fleshy, polypoidal, reddish looking mass with spores on the surface were clinically diagnosed as rhinosporidiosis. Age, sex distribution, site of presentation and socioeconomic status was studied. The swellings of lacrimal sac were doughy in consistency. The conjunctival mass was excised and thermocautery applied. For the cases of lacrimal sac dacryocystectomy was done. Results: The cases were more common in male children of low socioeconomic status. Palpebral conjunctiva is the common site of involvement. History of pond bath was present in almost all the cases. History of bleeding from nose and eye was present in many cases. Conclusions: Rhinosporidiosis is a common condition of our locality. Treatment is simple by excising the growth and cauterising the site. Taking bath in pond water is supposed to be the cause of the disease. The disease can be prevented by avoiding pond bath.